IMPLEMENTASI KRIPTOGRAFI RSA DENGAN PHP - Muhammad Yasin Simargolang (Universitas Asahan, 2017)
Abstract - Cryptography is an art and science to maintain data security. In maintaining the security of cryptographic data transforming clear data (plaintext) into a password (ciphertext) that cannot be recognized. This ciphertext is then sent by the sender to the recipient. After arriving at the recipient, the ciphertext is transformed back into a plaintext form so that it can be recognized. The method used is the encryption method asymmetrical Rivest Shamir Adleman (RSA). The security of the RSA algorithm lies in the difficulty of factoring large numbers into prime factors. Factoring is done to obtain a private key. Making this application using the PHP programming language. The final result is a desktop-based application that can be used to encrypt text files. This application can be used as a way to secure data, because only authorized people can view encrypted data. Keywords - Cryptography, RSA, Encryption - Decryption, Text, PHP